2017
DOI: 10.14260/jemds/2017/609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Bilateral Total Salpingectomy on Ovarian Function Among Pre-Menopausal Women Undergoing Abdominal Hysterectomy

Abstract: BACKGROUNDHysterectomy is a widely performed surgery. Whether bilateral salpingectomy done along with Total Abdominal Hysterectomy (TAH) affect ovarian function is controversial. This study aims to find out if bilateral salpingectomy has any adverse effect on the ovarian health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Our results are supported by findings reported by Mitra et al (13) who stated that there was no significant difference between groups regard distribution of Cause of hysterectomy. Indications for hysterectomy were fibroid (55%), Dysfunctional Uterine Bleeding (DUB) (28.33%), adenomyosis (10%) and chronic lower abdominal pain (6.66%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are supported by findings reported by Mitra et al (13) who stated that there was no significant difference between groups regard distribution of Cause of hysterectomy. Indications for hysterectomy were fibroid (55%), Dysfunctional Uterine Bleeding (DUB) (28.33%), adenomyosis (10%) and chronic lower abdominal pain (6.66%).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are supported by findings reported by Mitra et al (13) as they reported that Flow elevation as shown by the reduction in the PI (Pulsatility Index), is likely to reflect the larger size of the ovaries after the surgery. "…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation